Relationship between shift work, night work, and subsequent dementia: A systematic evaluation and meta-analysis - Wang, Zhen-Zhi; Sun, Zhen; Zhang, Mei-Ling; Xiong, Kang; Zhou, Feng (Frontiers in Neurology, 2022)
Background The association between shift work, night work, and the risk of dementia are conflicting in the literature. Objectives This study was performed to obtain evidence on the potential relationship between shift work, night work, and dementia. Methods To investigate the link between shift work, night work, and dementia, we systematically searched PubMed, Embase, and Web of Science from inception to January 1, 2022. A fixed or random-effects model was used to retrieve the combined dominance ratio. The eligibility of the retrieved records and extracted data were independently reviewed by two researchers. Throughout the study, the Preferred Reporting Items for Systematic Evaluations and Meta-Analyses (PRISMA) statement was followed. STATA 16.0 was used to conduct the meta-analysis. Results A total of four studies involving 94171 were included in this meta-analysis. Pooled results indicated that night shift workers had a 12% increased risk of dementia compared to subjects without night work (HR = 1.12, 95% CI 1.03-1.23, P=0.094). Shift work was not significantly associated with dementia risk (HR: 1.11, 95% CI: 0.87-1.42, P=0.398), but the effect of shift work on dementia risk appeared to increase with age, with a correlation observed among workers older than 50 years (HR = 1.31; 95% CI: 1.03–1.68, P = 0.030). Conclusion The data presented in our study suggest that night work is a risk factor for dementia, but no association exists between shift work and the risk of dementia. Objective prospective exposure measurements are required in future studies.